Problems of Development of Housing and Communal Services in Russia - Kemaykin, Nikolay K.; Pavlenkov, Mikhail N.; Voronin, Pavel M. (The journal of contemporary issues in business and government, 2021)
Despite the positive tendencies in housing and communal services (HCS) of the Russian Federation, in the 2020 positive changes occur very slowly and sometimes with sharp contradictory deviations from the intended course. In this article, we highlight the major problems of the development of HCS that demand priority elimination. This study aimed at assessing the effectiveness of government programs implemented in the HCS sector and was based on the methods of analysis, induction, deduction and dialectical-logical approaches. Five main problems in the development of HCS were found out by using induction method. The identified problems relate to the field of strategic management and characterize the inefficiency of the development and implementation of development plans. These problems were compared with the tools of private concepts of controlling the sphere of HCS. Namely, the problems of development were compared with the technology of forming a controlling system. Results indicated irregularities or incorrect execution of separate stages of controlling technology. The obtained results have theoretical and practical importance for increasing the efficiency of the development of the sphere. The results of the study can be used to clarify goals, objectives, and adjust activities to accelerate the development of the industry.